The Influence Of Online Reviews on Purchasing Decisions at Restoran Waroeng Kampoeng Jimbaran Bali - Vanessa, Patricia; Suarka, Fanny Maharani; Sulistyawati, Agung Sri (Jurnal Kepariwisataan dan Hospitalitas, 2023)
Restaurant is a business in the catering service sector that provides services for ordering food and beverages. Over time, the development of the internet is increasingly felt and tourists can easily get the information they want from the internet. Reviews on the internet are one of the things that has the potential to influence their perception of a place, especially a restaurant. In recent years, there have been many sources of data information on the internet that can influence readers with reviews of their experiences. Google Reviews, Zomato and Tripadvisor are some of the sites that are quite widely used by tourists. Therefore, in this study, the authors examined the effect of online reviews on purchasing decisions at Waroeng Kampoeng Jimbaran Bali Restaurant. The restaurant that the author studied is the Waroeng Kampoeng Restaurant which is located in the Jimbaran area, Bali. In this study using qualitative as well as quantitative data, and the determination of informants and samples was carried out by purposive sampling method. Based on the results of statistical tests obtained from the simple linear regression equation, the results obtained Y = (4.463) + 0.732X with a correlation result of 0.732, which means it has a "strong" relationship. Next, the results of the t-test for the online review variable were obtained from the results of the t-test, namely 10,634, with the obtained t-table of 1.98447. This means that tcount 10.634> ttable 1.98447 and a significance value of 0.000 <0.05, so the conclusion is that the online review variable has a positive effect of 10.634 and is significant with a significance of 0.000 on the purchasing decision variable. This research concludes that Ho is rejected and Ha is accepted, which means that there is a positive and significant influence between online reviews on purchasing decisions at Waroeng Kampoeng Restaurant Jimbaran Bali.